Mammographic and Sonographic Findings in Breast Cancer Screening - Aurora, Habiba; Yueniwati, Yuyun (Department of Radiology, Medical Faculty, University of Brawijaya, 2022)
Breast cancer in the most common malignancy in woman. Screening is very important to identify precancerous lesions. The use of diagnostic imaging is one of the first steps in cancer diagnosis. Mammography is one of detection tool, which able to detect breast abnormality in early stage, while breast sonography is more helpful in cases with dense breast. In this study we compared the finding on mammography and ultrasonography among woman 40 to 60 years undergoing breast cancer screening. This study included 30 asymptomatic woman aged over 40 years, which have no history of reast cancer. All were assigned to undergo screening by either mammography and ultrasonography. The diagnoses were scored due to ultrasound BI-RADS, the finding from mammography and breast ultrasound were compared to analyze the difference between both examination. From the result of mammography and ultrasound were shown that at the same BIRADS scale, different images could be obtained. Further studies are needed to demonstrate the significance of the differences in examination findings on the same BIRADS scale. Keywords: Breast Cancer, Mammography, Screening, Sonography